Functional visceral fat activity evaluated by preoperative F‐18 FDG PET/CT predicts regional lymph node metastasis in differentiated thyroid cancer. (16th April 2018) - Pahk, Kisoo; Choi, Sunju; Kim, Sungeun
Summary: Objective: We investigated the predictive role of functional visceral fat activity evaluated by preoperative F‐18 FDG PET/CT for regional lymph node metastasis in patients with differentiated thyroid cancer. Design and patients: Fifty‐eight patients with newly diagnosed differentiated thyroid cancer were enrolled in this study, retrospectively (men 14; women 44; age 53 ± 14.5). They all received preoperative F‐18 FDG PET/CT and surgery. Functional visceral fat activity was defined as maximum standardized uptake value (SUVmax) of visceral fat divided by SUVmax of subcutaneous fat (V/S ratio). Pathology results were confirmed through the surgical specimens. Results: The patients with regional lymph node metastasis showed higher functional visceral fat activity (V/S ratio) than the patients without regional lymph node metastasis (2.12 ± 0.6 vs 1.62 ± 0.34, P  =   .001). V/S ratio of 1.78 was suggested as an optimal cut‐off value for predicting regional lymph node metastasis (sensitivity; 70.3%, specificity; 83.3%, area under the curve; 0.778, P  <   .0001). Furthermore, functional visceral fat activity was significantly associated with regional lymph node metastasis in patients with differentiated thyroid cancer by univariate and multivariate analyses. Conclusions: Functional visceral fat activity significantly affects the regional lymph node metastasis status in patients with differentiated thyroid cancer. Furthermore, it may also be useful to predict regional lymph node metastasis.